Benzyltoluene/dibenzyltoluene-based mixtures as suitable liquid organic hydrogen carrier systems for low temperature applications - Jorschick, Holger; Geißelbrecht, Michael; Eßl, Melanie; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2020)
In this contribution we propose mixtures of the two LOHC systems benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) and dibenzyltoluene (H0-DBT)/perhydro dibenzyltoluene (H18-DBT) as promising hydrogen storage media for technical applications at temperatures below ambient. The mixing of the two LOHC systems provides the advantage of a reduced viscosity of the hydrogen-rich system, for example a 20 wt% addition of H12-BT to H18-DBT reduces the viscosity at 10 °C by 80%. Interestingly, it is also found that the dehydrogenation of such mixture provides a hydrogen release productivity that is 12–16% higher compared to pure H18-DBT dehydrogenation under otherwise identical conditions. This enhanced rate is attributed to a combination of reduced hydrogen partial pressure in the reactor (due to the higher H12-BT vapor pressure), preferred H12-BT dehydrogenation (due to faster H12-BT diffusion) and effective transfer hydrogenation between the two LOHC systems.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Benzyltoluene; Dehydrogenation; Dibenzyltoluene; Hydrogen storage; Hydrogenation; LOHC systems

Carbon Dioxide-Free Hydrogen Production with Integrated Hydrogen Separation and Storage - Dürr, Stefan; Müller, Michael; Jorschick, Holger; Helmin, Marta; Bösmann, Andreas; Palkovits, Regina; Wasserscheid, Peter (Chemsuschem, 2017)
An integration of CO2-free hydrogen generation through methane decomposition coupled with hydrogen/methane separation and chemical hydrogen storage through liquid organic hydrogen carrier (LOHC) systems is demonstrated. A potential, very interesting application is the upgrading of stranded gas, for example, gas from a remote gas field or associated gas from off-shore oil drilling. Stranded gas can be effectively converted in a catalytic process by methane decomposition into solid carbon and a hydrogen/methane mixture that can be directly fed to a hydrogenation unit to load a LOHC with hydrogen. This allows for a straight-forward separation of hydrogen from CH4 and conversion of hydrogen to a hydrogen-rich LOHC material. Both, the hydrogen-rich LOHC material and the generated carbon on metal can easily be transported to destinations of further industrial use by established transport systems, like ships or trucks.
Keywords: hydrogen storage; hydrogenation; liquid organic hydrogen carriers; methane decomposition; upgrading

Hydrogenation of aromatic and heteroaromatic compounds-a key process for future logistics of green hydrogen using liquid organic hydrogen carrier systems - Jorschick, Holger; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (Sustainable Energy & Fuels, 2021)
This review deals with the chemical storage of green hydrogen in the form of Liquid Organic Hydrogen Carrier (LOHC) systems. LOHC systems store hydrogen by an exothermal catalytic hydrogenation reaction that converts the hydrogen-lean compounds of the LOHC system to their hydrogen-rich counterparts. All compounds of a technically suitable LOHC system are liquids and this offers the advantage of simple logistics of chemically bound hydrogen in the existing infrastructure for fuels. On demand, hydrogen can be released from the hydrogen-rich LOHC molecule in an endothermal catalytic dehydrogenation at low hydrogen pressure (typically below 5 bar). Our contribution deals first with available sources of green hydrogen for a future hydrogen economy and then describes established technical processes to produce clean hydrogen from technically hydrogen-rich gas mixtures. Subsequently, the review focuses on the hydrogenation of aromatic and heteroaromatic compounds as the key step of the LOHC-based hydrogen storage cycle. Special emphasis is given to the hydrogen-charging of hydrogen-lean LOHC compounds with various gas mixtures demonstrating that such a Mixed Gas Hydrogenation (MGH) process offers the technical potential to selectively extract hydrogen in a chemically bound form that enables very efficient hydrogen logistics. In this way, low cost hydrogen sources can be connected to high value hydrogen application, e.g. hydrogen filling stations for clean mobility applications, to enable a future hydrogen economy.
CRIS-Team Scopus Importer:2021-03-19

Hydrogen storage using a hot pressure swing reactor - Jorschick, Holger; Preuster, Patrick; Dürr, Stefan; Seidel, Alexander; Müller, Karsten; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2017)
Our contribution demonstrates that hydrogen storage in stationary Liquid Organic Hydrogen Carrier (LOHC) systems becomes much simpler and significantly more efficient if both, the LOHC hydrogenation and the LOHC dehydrogenation reaction are carried out in the same reactor using the same catalyst. The finding that the typical dehydrogenation catalyst for hydrogen release from perhydro dibenzyltoluene (H18-DBT), Pt on alumina, turns into a highly active and very selective dibenzyltoluene hydrogenation catalyst at temperatures above 220 °C paves the way for our new hydrogen storage concept. Herein, hydrogenation of H0-DBT and dehydrogenation of H18-DBT is carried out at the same elevated temperature between 290 and 310 °C with hydrogen pressure being the only variable for shifting the equilibrium between hydrogen loading and release. We demonstrate that the heat of hydrogenation can be provided at a temperature level suitable for effective dehydrogenation catalysis. Combined with a heat storage device of appropriate capacity or a high pressure steam system, this heat could be used for dehydrogenation.

Operational stability of a LOHC-based hot pressure swing reactor for hydrogen storage - Jorschick, Holger; Dürr, Stefan; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (Energy Technology, 2018)
Apart from hydrogen logistics, stationary hydrogen storage applications using Liquid Organic Hydrogen Carrier (LOHC) systems are also of significant interest. In contrast to the traditional use of separate hydrogenation and dehydrogenation reactors, our so-called oneReactor technology offers the advantages of a simpler storage unit layout and high dynamics in switching from hydrogen charging to hydrogen release. Here we report repeated hydrogenation and dehydrogenation cycles with one batch of liquid carrier for LOHC stability tests under defined hydrogenation and dehydrogenation conditions. We demonstrate up to 13 hydrogenation/dehydrogenation cycles over a total of 405 h of operation including two long dehydrogenation sequences over weekends. In general, longer dehydrogenation runs, i.e. exposure of the LOHC to catalyst at low hydrogen pressure and elevated temperatures (> 280 °C), showed negative effects on both activity of the subsequent cycles and by-product formation. Concerning catalyst activity and hydrogen productivity, stable productivity was achieved (within 3 to 9 cycles) under all conditions tested. Longer hydrogenation runs led to significantly higher stability of the reaction system.
Keywords: hydrogen storage; LOHC systems; hydrogenation; dehydrogenation; platinum; stability

Purity of hydrogen released from the Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene by catalytic dehydrogenation - Bulgarin, Alexander; Jorschick, Holger; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2019)
While Liquid Organic Hydrogen Carrier (LOHC) systems offer a very promising way of infrastructure-compatible storage and transport of hydrogen, the hydrogen quality released from charged LOHC compounds by catalytic dehydrogenation has been a surprisingly rarely discussed topic to date. This contribution deals, therefore, with a detailed analysis of the hydrogen purity released from the hydrogen-rich Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene (H18-DBT). We demonstrate, that high purity hydrogen (>99.999%) with carbon monoxide levels below 0.2 ppmv can be obtained from the dehydrogenation of H18-DBT if the applied H18-DBT had been carefully pre-dried and pre-purified prior to the dehydrogenation experiment. Indeed, the largest part of relevant impurities to comply with the hydrogen quality standard for fuel cells in road vehicles (ISO 14687-2) was found to originate from water and oxygenate impurities present in the applied, technical LOHC qualities.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Carbon monoxide; Hydrogen storage; LOHC systems; Oxygenates; Water